Reorganizing U.S. Domestic Intelligence Assessing the Options - Treverton, Gregory F. (RAND Corporation, 2008)
One of the questions in the fight against terrorism is whether the United States needs a counterterrorism domestic intelligence agency separate from law enforcement. Drawing on an analysis of current counterterrorism efforts, an examination the domestic intelligence agencies in six other democracies, and interviews with intelligence and law enforcement experts, this volume lays out the relevant considerations for creating such an agency.